Prevalence of burnout syndrome in clinical nurses at a hospital of excellence - Ribeiro, Vivian F.; Ferreira Filho, Celso; Valenti, Vitor Engrácia [UNESP]; Ferreira, MArcelo; Abreu, Luiz Carlos de; Carvalho, Tatiana D; PEreira, Valdelias Xavier; Oliveira Filho, Japy Angelini de; Gregory, Pedro; Leão, Eliseth Ribeiro; Francisco, Natascha G.; Ferreira, Celso (My University, 2014)
Background: Burnout syndrome can be defined as long-term work stress resulting from the interaction between constant emotional pressure associated with intense interpersonal involvement for long periods of time and personal characteristics. We investigated the prevalence/propensity of Burnout syndrome in clinical nurses, and the factors related to Burnout syndrome-associated such as socio-demographic characteristics, work load, social and family life, leisure activities, extra work activities, physical activities, and work-related health problems. Method: We conducted a cross-sectional, quantitative, prospective epidemiological study with 188 surgical clinic nurses. We used the Maslach Burnout Inventory (MBI), which is a socio-demographic questionnaire and the most widely used instrument to assess Burnout syndrome (three basic dimensions: emotional exhaustion, despersonalization and professional underachievement). The socio-demographic profile questionnaire wascomposed of questions regarding identification, training, time at work, work characteristics and personal circumstances. Results: The prevalence of Burnout syndrome was higher (10.1%) and 55, 4% of subjects had a propensity to develop this syndrome. The analysis of the socio-demographic profile of the nurse sample studied showed that most nurses were childless married women, over 35 years of age, working the day shift for 36 hours weekly on average, with 2-6 years of post-graduation experience, and without extra employments. Factors such as marital status, work load, emotion and work related stress aggravated the onset of the syndrome. Conclusion: The prevalence and propensity of Burnout syndrome were high. Some factors identified can be useful for the adoption of preventive actions in order to decrease the prevalence of the clinical nurses Burnout syndrome.